Compaction behaviour and prediction of its characteristics of fine grained soils with particular reference to compaction energy - Gurtug, Y; Sridharan, A (Japanese Geotechnical Soc, 2004)
Field compaction of fine grained soils usually involves different equipments with the compaction energy varying significantly. Hence the compaction characteristics (maximum dry unit weight and optimum moisture content) need to be obtained at different compaction energies. Thus knowledge of compaction behaviour and its characteristics of fine grained soils at different compaction energies assumes great importance from the viewpoint of practical significance. In this paper the effect of compaction energy on the behaviour and compaction characteristics of fine grained soils has been brought out. It has been seen that the optimum moisture content bears a good relation with plastic limit and the maximum dry unit weight correlating well with the dry unit weight of soil at plastic limit for all compaction energies studied. Apart from the experimental data obtained by the authors, extensive results from literature have also been used in the analysis. In view of large quantities of soils from different borrow pits to be tested for their potential use, the above correlation with plastic limit enables not only saving of time but also cost of investigation for preliminary design.
Keywords: compaction; compaction energy; earth work; fine grained soils; ground improvement; laboratory tests (IGC : D9/K5)